Pendidikan Multikultural dalam Perspektif Filsafat Pendidikan Islam - Intan Kumala Sari; Nurkholijah Siregar (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
This study aims to analyze multicultural education in the perspective of Islamic education philosophy. The research method used is qualitative using a library research approach. The main data source in this study is Islamic educational literature based on philosophy and the secondary source is research articles that are relevant to this research. Data analysis uses content analysis techniques. The results of the study show that the essence of multiculturalism is culture and the recognition of cultural diversity and the response to accepting the diversity of cultural realities. Islam is a religion that is not based on culture, but has a concept of how its people are cultured and have good morals. Islamic culture is a procedure that refers to Islamic principles. Islamic culture itself is purely based on the Qur'an and Hadith, while non-Islamic culture is only based on human creations and that culture will never be the same. In the perspective of the philosophy of Islamic education, multicultural education trains and builds the character of students to be able to be democratic, humanist, and pluralist in their environment. In other words, multicultural education is a resistance to fanaticism that leads to this type of violence.